Exergy-economic analysis of a solar-geothermal combined cooling, heating, power and water generation system for a zero-energy building - Baniasadi, Ehsan; Ziaei-Rad, Masoud; Behvand, Mohammad Amin; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this study, energy, exergy and exergy-economic analyses of a novel system that simultaneously generates cooling effect, heat, electricity, hot water and desalinated water for a zero-energy building are presented. It is aimed to evaluate the feasibility of using a solar-geothermal system to meet the energy and water demands of a residential building using exergy-economic indexes. The multi-generation system operates based on solar and geothermal energies, and it consists of proton exchange membrane (PEM) electrolyser, PEM fuel cell, photovoltaic system, and a desalination system with a pressure exchanger. Results indicate that energy and exergy efficiencies in cooling mode are 13.27% and 32.44%, respectively, and in heating mode are 17.25% and 42.4%, respectively. The largest exergy destruction occurs in the photovoltaics and organic Rankine cycle. It is observed that the turbine and boiler have the highest portion in the exergy destruction of the organic Rankine cycle. The capital investment and operating and maintenance cost rate, and the cost of produced distilled water are 4.288 ($/h), 67.63 (c$/m3), respectively. Moreover, the unit exergy costs of power, heating and cooling effect are investigated. The exergy-economic factor and the cost of exergy destruction for the entire system are 57.38% and 4.288 ($/h), respectively. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Zero-energy building; CCHPW system; Geothermal energy; Solar energy; Exergy-economic analysis; MULTIGENERATION SYSTEM; THERMODYNAMIC ANALYSIS; PERFORMANCE ASSESSMENT; PEM ELECTROLYZER; HYDROGEN; Chemistry; Electrochemistry; Energy & Fuels